Morphological and Developmental Responses of Macro Cuttings of Vernonia Amygdalina Del. to Synthetic Growth Hormones - Eremrena, P. O.; Agogbua, J. U. (European Journal of Applied Sciences, 2023)
The morphological and developmental responses of Vernonia amygdalina macro shoot cutting to plant growth hormonal solution of 6-benzyl amino purine (BAP) and naphthalene acetic acid (NAA) were investigated in the laboratory. The concentration levels of 2.5, 5.0; 7.5 and 10.0mg/l were used alongside a control treatment (0mg/i). The growth parameters examined were shoot length, root length and leaf number. The protein and carbohydrate contents of the plants were also assessed. The result of this study showed that the root length and leaf number of the species were significantly (P=0.05) increased with increase in the concentration of plant growth regulators. Similarly, the carbohydrate and protein contents in treatment with plant growth regulators were comparatively higher than those of the control. This study suggests that plants growth regulators can be utilized to enhance growth and development activities in Vernonia amygdalina Del. and that plant growth regulators such as benzyl amino purine and naphthalene acetic acid aided to maintain an appropriate shoot to root ratio and could be used to induce rooting in stem cuttings.